PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSET TURNOVER, RETURN ON ASSET, DAN NET PROFIT MARGIN TERHADAP PERTUMBUHAN LABA (Studi empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Periode Tahun 2015-2017) - Ulifa Muna Amaliya, 14.05.62.0017; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2018)
This study aims to analyze and examine the effect of Current Ratio, Debt to Equity Ratio, Total Asset Turnover, Return on Assets and Net Profit Margin on profit growth. The population in this study were 228 manufacturing companies listed on the Indonesia Stock Exchange. The sampling technique uses purposive sampling method, with the results of the sample studied are 76 companies.The results of this study indicate that Return on Assets have a significant positive effect on earnings growth. While Current Ratio,Debt to Equity Ratio, Total Asset Turnover, and Net Profit Margin have no significant effect on profit growth. Keywords: Profit Growth, Current Ratio, Debt to Equity Ratio, Total Asset Turnover, Return on Assets and Net Profit Margin.